Acaredemy Sdn. Bhd. / Fathin Nur Hakimah Zainal - Zainal, Fathin Nur Hakimah (2021)
Acaredemy Sdn. Bhd. is built with the purpose of providing childcare and private tutoring to help busy parents. This company started its operation on 30th January 2020 and is located at Kampung Datuk Keramat, Kuala Lumpur. It is co-owned by Fathin Nur Hakimah binti Zainal and her partner, Izzati Asilah binti Md Hamami. The company offers two raain options for its clients, which are infants’ package and school kids’ package. These packages include the sitters to take full responsibility for the health and welfare of the children including healthy meals and hygiene when the parents are working. The objectives of marketing are to introduce The Acaredemy Sdn. Bhd. to the public, to promote the best and improved childcare services by The Acaredemy Sdn. Bhd., and to attract more customers into The Acaredemy Sdn. Bhd. Other than that, we target customers based on the geographic segmentation and demographic segmentation where the location of the academy and the income of its clients are considered as factors that would affect our marketing.The Acaredemy Sdn. Bhd, follows the four (4) elements of marketing strategies: product, pricing, place, promotion. As for the product or services, we offer childcare services, private tutoring, and service differentiation. Next, we chose a strategic place to run our business which is in the city of Kuala Lumpur and offer a better price for each service than our competitors. For promotion, we advertise and promote the academy through business cards, signage and social media. The Acaiedemy Sdn. Bhd is run by a general manager, Fathin Nur Hakimah binti Zainal, an administration manager, lzzati Asilah binti Md Hamami, a marketing manager, Nurul Nadhrah binti Kamalariffm, an operational manager, Nor Suhada bmti Ibrahim, and a financial manager, Nadzatul Athirah binti Mohmad Alirudin.The general manager manages company business with responsibilities and plans a strategy to achieve the company target. Meanwhile, the administration manager acts as an advisor to the general manager and manages all administration expenses. The marketing manager takes care of business aspect of e-commerce, the operational manager ensures the operation flow works efficiently and systematic while the financial manager manages and coordinates monthly reporting, budgeting, and reforecast processes.